Functions Modeling Change: A Preparation for Calculus, 5th Edition

Published by Wiley
ISBN 10: 1118583191
ISBN 13: 978-1-11858-319-7

Chapter 4 - Exponential Functions - Exercises to Skills for Chapter 4 - Page 185: 7



Work Step by Step

Use the fact that $\frac{a^m}{a^n}=a^{m-n}$ to simplify the expression to $$=\frac{6^4}{6^4}=6^{4-4}=6^0$$ Any non-zero value to the power $0$ is $1$. Therefore, $6^0=1$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.